On the Security of NMAC and Its Variants - Fanbao Liu; Changxiang Shen; Tao Xie; Dengguo Feng (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
Based on the three earlier MAC (Message Authentication Code) construction approaches, we propose and analyze some variants of NMAC. We propose  some key recovery attacks to  these  NMAC  variants, for  example, we can  recover  the  equivalent  inner  key  of NMAC  in  about O(2n/2) MAC  operations, in  a related key  setting. We  propose  NMAC-E, a  variant of NMAC  with  secret  envelop,  to  achieve  more  process  efficiency  and  no  loss  of security, which needs only one call to the  underlying hash  function, instead of two invocations in HMAC.